(untitled) (Jalalabad Medical Journal, 2025)
Immunological disturbances have often been described in leprosy patients-more so in the lepromatous (LL) than in the tuberculoid (TT) end of the clinicopathological spectrum of the disease. Studies suggested that active lepromatous patients showed a significant lymphopenia and a significant proportionate reduction in the number of OKT3-positive (Pan T), OKT4-positive (Helper/inducer/CD4), and OKT8-positive (Suppressor/cytotoxic/CD8) cells, but no alteration in distribution as judged by percentage and no abnormality in the helper-suppressor ratio. This research work was performed at the department of microbiology and clinical pathology, department of medicine, Sylhet MAG Osmani Medical College and Hospital, Sylhet; and leprosy hospital, Sheikhghat, Sylhet, during the period of January 2012 to December 2012. The objective of the study was to determine cell-mediated immunity by measuring CD4+ and CD8+ cells, and their ratio in patients with leprosy before and after treatment. In this quasi-experimental study, 30 patients with leprosy were enrolled to measure the status of CD4 and CD8 cell counts with their ratios before intervention, and the values were compared to the second sample from the same patients who had multi-drug treatment for leprosy. Lymphocyte count (p<0.001) significantly increased after treatment of leprosy. CD4+ T cell count (p<0.001) and CD8+ T cell count (p=0.001) were significantly increased after treatment of all 30 leprosy cases, with no significant changes in the CD4+/CD8+ ratio (p=0.072). CD4+ T cell count (p=0.001) and CD8+ T cell count (p=0.018) were significantly increased after treatment of the 17 specific lepromatous leprosy cases, and there was no significant change in the CD4+/CD8+ ratio (p=0.070) in the same cases. The immune parameter showed a significantly upward change in the form of a raised lymphocyte count, and CD4+ and CD8+ T cell counts, while CD4+/CD8+ ratios are insignificantly raised after treatment of leprosy and also of lepromatous leprosy. Jalalabad Med J 2023; 20 (2): 54-59